2004
DOI: 10.1021/bi0353373
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Functional Characterization of SGTx1, a Modifier of Kv2.1 Channel Gating,

Abstract: SGTx1 is a peptide toxin isolated from the venom of the spider Scodra griseipes that has been shown to inhibit outward K(+) currents in rat cerebellar granule neurons. Although its amino acid sequence is known to be highly (76%) homologous with that of hanatoxin (HaTx), a well-characterized modifier of Kv2.1 channel gating, the structural and functional characteristics of SGTx1 remain largely unknown. Here we describe the NMR solution structure of SGTx1, the mechanism of its interaction with Kv2.1 channels, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 53 publications
5
97
0
1
Order By: Relevance
“…ProTx-II and a related tarantula venom peptide, ProTx-I, inhibit sodium channels by a mechanism similar to that of the potassium channel gating modifiers hanatoxin and SGTx1 (Swartz and MacKinnon, 1997;Lee et al, 2004). Indeed, ProTx-I shares significant sequence homology with hanatoxin.…”
Section: Discussionmentioning
confidence: 99%
“…ProTx-II and a related tarantula venom peptide, ProTx-I, inhibit sodium channels by a mechanism similar to that of the potassium channel gating modifiers hanatoxin and SGTx1 (Swartz and MacKinnon, 1997;Lee et al, 2004). Indeed, ProTx-I shares significant sequence homology with hanatoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Venom peptides of the same family have been difficult to crystallize, and the currently known structures of Huwenoxin-IV, Hanatoxin-I, Hainantoxin-IV, SGTx1, and GrTx (42,(45)(46)(47)(48)(49) were determined by NMR techniques. We utilized a different approach and generated a high affinity antibody with a low dissociation rate and obtained a high resolution x-ray crystal structure of 2670 in complex with the Fab fragment of this antibody (supplemental Table 1).…”
Section: Effects Of Post-translational Modification On Potency Andmentioning
confidence: 99%
“…Wang et al (19) also found basic residues in SGTx that are critical for inhibition of K v 2.1, whereas mutation of acidic residues in fact increased the affinity of that toxin for its target. In the SGTx solution structure, the basic residues form a ring around the hydrophobic patch, presumably creating the active face (31). Because the solution structure for ProTx-II is unknown, we chose to construct a molecular model based upon the known solution structure of a similar ICK toxin that targets K v 4 channels, HpTx-2.…”
Section: Mutationmentioning
confidence: 99%